2019
DOI: 10.1111/imm.13085
|View full text |Cite
|
Sign up to set email alerts
|

Protein 4.1R negatively regulates CD8+ T‐cell activation by modulating phosphorylation of linker for activation of T cells

Abstract: Protein 4.1R, an 80 000 MW membrane skeleton protein, is a vital component of the red blood cell membrane cytoskeleton that stabilizes the spectrin-actin network and regulates membrane properties of deformability and mechanical stability. It has been shown that 4.1R is expressed in T cells, including CD8 + T cells, but its role in CD8 + T cells remains unclear. Here, we have explored the role of 4.1R in CD8 + T cells using 4.1R À/À mice. Our results showed that cell activation, proliferation and secretion leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Erythrocyte membrane protein band 4.1 (EPB41) links cell membrane proteins to the cytoskeleton and is involved in many cellular processes such as cell proliferation, cytokine secretion, cell adhesion, and cell migration [ 29 , 30 , 31 , 32 , 33 , 34 ]. EPB41 suppresses epidermal growth factor receptor (EGFR) activation [ 29 ] and thus plays an important role as a tumor suppressor in cancer development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erythrocyte membrane protein band 4.1 (EPB41) links cell membrane proteins to the cytoskeleton and is involved in many cellular processes such as cell proliferation, cytokine secretion, cell adhesion, and cell migration [ 29 , 30 , 31 , 32 , 33 , 34 ]. EPB41 suppresses epidermal growth factor receptor (EGFR) activation [ 29 ] and thus plays an important role as a tumor suppressor in cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Rare variants significantly associated with KC across several association test methods are shown in Table 3 and Figure 2. Several of the genes described here can be assigned to categories that are involved in the development of solid tumors: MC1R is involved in pigmentation/UV protection [27,28], EPB41 [29][30][31][32][33][34] and MYCT [35][36][37][38] in tumor suppression, and ADGRG3 in immunomodulation [39][40][41][42]. Studies on MGME1 suggest a direct involvement in cancer development and progression [43,44], and finally upregulation of the EPH8A gene expression was associated with a poor prognosis in ovarian, oral tongue, and gastric cancers [45][46][47].…”
Section: Rare Variantsmentioning
confidence: 99%
“…Additional investigations have demonstrated that 4.1R suppresses the activation of CD4 + T cells, thereby mitigating pathogenic autoimmunity in the progression of multiple sclerosis and experimental autoimmune encephalomyelitis progression [48]. Recent research has also indicated that 4.1R is a negative regulator of TCR signaling in CD8 T cells through its direct association with LAT [29]. In mast cells, Draberova et al indicated that 4.1R acts as a positive regulator in the initial activation events following FcεRI triggering through its direct interaction with both LAT1 and LAT2 [27].…”
Section: Cell Activationmentioning
confidence: 99%
“…Further experiments showed that protein 4.1R could suppress activation of CD4 + T cells and thereby prevent progression of pathogenic autoimmunity (36). Recently published data concluded that the 4.1R protein is also a negative regulator of TCR signaling in CD8 + cells (37). However, the role of the 4.1R protein in the function of other immunoreceptors is not understood.…”
Section: Introductionmentioning
confidence: 99%